PERUBAHAN UPACARA KEMATIAN SAYUR MATUA DALAM ETNIS SIMALUNGUN DI DESA SONDI RAYA - Elvera Chrismiseri Purba; Pulung Sumantri (Puteri Hijau : Jurnal Pendidikan Sejarah, 2020)
Research title "Change in Simalungun Ethnic Death Ceremony in Sondi Raya Village". The purpose of writing this thesis is to find out the function of the death ceremony in the ethnic Simalungun, the value contained in the death ceremony, and the changes contained in the process of the death ceremony in the ethnic Simalungun in the village of Sondi Raya. The method used in this study is a historical method that uses written and oral sources, in the form of books and photographs of the Simalungun ethnic death ceremony. Oral sources were obtained through interviews with Raja Parhata (traditional leaders) and religious leaders, as well as laboratory studies using video of death in the village of Sondi Raya. The results obtained are (1) The function of the death ceremony in Simalungun is as a final tribute to the deceased especially to someone who has the title of Sayur Matua. (2) The value contained in the ceremonial death in the ethnic Simalungun namely the value of Sapangahapan is still thick in the Simalungun community, where every misfortune of the surrounding community provides consolation so that families who are grieving do not continue to dissolve in sadness. (3) Changes in the Simalungun death ceremony experienced some of the most striking changes is the gual vegetable matua which was always used during the death ceremony became rare and even changed into modern music, and the size of the porcelain (white cloth) before the size of the porcelain varies depending on the closeness of kinship with deceased person. While now the size is the same for all those who are still close relatives and community mourners in the same village.Keywords: Sayur Matua, Simalungun